Operations research proceedings 2013 : Selected Papers of the International Conference on Operations Research, OR2013, organized by the German Operations Research Society (GOR), the Dutch Society of Operations Research (NGB) and Erasmus University Rotterdam, September 3-6, 2013 - Louwerse, Ilse; Wagelmans, Albert P.M; Huisman, Dennis (Operations Research Proceedings, GOR (Gesellschaft für Operations Research e.V.), 2014)
This book contains a selection of refereed papers presented at the "International Conference on Operations Research (OR 2013)" which took place at Erasmus University Rotterdam September 3-6, 2013. The conference was jointly organized by the German and the Dutch OR Society. More than 800 scientists and students from over 50 countries attended OR 2013 and presented more than 600 papers in parallel topical streams, as well as special award sessions. The theme of the conference and its proceedings is "Impact on People, Business and Society".